LEAN MANUFACTURING IN PRODUCT DEVELOPMENT: CASE STUDY IN A TEXTILE INDUSTRY - Milnitz, Diego; da Silva, Glauco Garcia Martins Pereira (Editora Impacto Científico, 2025)
The reduction of lead time in the product development process (PDP) is one of the main challenges faced by organizations operating in dynamic and competitive markets, such as the textile sector. In this context, the application of lean manufacturing principles has proven to be a promising strategy to eliminate waste and increase efficiency. This article aims to analyze the joint application of Value Stream Mapping (VSM) and the Gemba Kaizen (GK) method in a multi-project PDP of a textile industry in Santa Catarina, seeking to highlight how these practices can contribute to continuous improvement. Methodologically, the study adopts action research, conducted in two intervention cycles: the first focusing on waste identification through VSM, and the second on implementing improvements via GK. The results revealed the existence of excessive information inventories, rework, and inconsistencies in material and data flows, which directly impacted lead time. The application of lean practices resulted in a 63% reduction in the rework rate in printing and a decrease of two days in the total PDP lead time. As a contribution, the study demonstrates the applicability of Lean Product Development in sectors still scarcely explored in the literature, such as textiles, while also highlighting the relevance of integrating classical quality tools with lean methodologies. It further suggests the need for future research on the digitalization of VSM and GK, aligning product development with the principles of Industry 4.0 and the circular economy. DOI: https://doi.org/10.56238/edimpacto2025.069-006